Fleas and trypanosomes of peridomestic small mammals in sub-Saharan Mali. Issue 1 (December 2016) - Schwan, Tom; Lopez, Job; Safronetz, David; Anderson, Jennifer; Fischer, Robert; Maïga, Ousmane; Sogoba, Nafomon
Abstract Background Fleas are obligate blood-feeding ectoparasites and vectors of several bacterial zoonotic pathogens as well as trypanosomes that parasitize rodents and other small mammals. During investigations of tick- and rodent-borne diseases in Mali, West Africa, we included fleas and rodent-borne trypanosomes, both of which are poorly known in this country, but are attracting greater public health interest. Methods Small mammals were captured in 20 Malian villages from December 2007 to October 2011. Fleas were collected and identified to species, and thin blood smears were prepared, stained and examined microscopically for trypanosomes. Results We captured 744 small mammals, 68 (9.1 %) of which yielded fleas. Two species of fleas, Xenopsylla cheopis andXenopsylla nubica, were collected from six species of rodents and one species of shrew. Multimammate rats, Mastomys natalensis, were hosts for 58.5 % of all fleas collected.Xenopsylla cheopis was found in the moister southern savannah whileX. nubica was mostly restricted to the drier Sahel. Trypanosomes were found in 3 % of 724 blood smears, although 91 % of parasitemic animals originated from two villages where black rats (Rattus rattus ) andM. natalensis were the primary hosts andX. cheopis the dominant flea. The trypanosomes were morphologically consistent with theTrypanosoma (Herpetosoma )lewisi group, flea-borne hemoflagellates that parasitize domestic rats. Conclusions Xenopsylla cheopis and trypanosomes parasitize peridomestic rats that commingle with people in southern Mali. Given the increasing awareness of flea-borne trypanosomes as possible human pathogens, we hope our findings will stimulate future investigators to examine the potential public health significance of flea-borne trypanosomosis in West Africa.